'Lad culture' in higher education: Agency in the sexualization debates. (June 2015) - Phipps, Alison; Young, Isabel
This article reports on research funded by the National Union of Students, which explored women students' experiences of 'lad culture' through focus groups and interviews. We found that although laddism is only one of various potential masculinities, for our participants it dominated the social and sexual spheres of university life in problematic ways. However, their objections to laddish behaviours did not support contemporary models of 'sexual panic', even while oppugning the more simplistic celebrations of young women's empowerment which have been observed in debates about sexualization. We argue that in their ability to reject 'lad culture', our respondents expressed a form of agency which is often invisibilized in sexualization discussions and which could be harnessed to tackle some of the issues we uncovered.